A Green Protocol for the Synthesis of α‐Diazo‐β‐hydroxyesters and One‐Pot Conversion to β‐Keto‐Esters and Imidazo[1, 2‐a]pyridine‐3‐carboxylates. Issue 19 (22nd May 2019) - Dutta, Nibedita Baruah; Sharma, Suraj; Chetry, Rudra Lal; Baishya, Gakul
Abstract: A new solvent cum reagent system comprising of water extract of banana ash and dimethylsulfoxide (WEB‐DMSO) has been engaged for the first time to promote the aldol type condensation reaction of aldehydes with ethyl diazoacetate. The condensation reaction has smoothly undergone producing a range of α‐diazo‐β‐hydroxy esters in good to excellent yields. The solvent system has been reused up to five times without loss of its catalytic activity. Further, two one‐pot sequential reactions have been developed in the same reaction medium. First, the methodology has been extended to synthesize β‐keto esters through Pd catalyzed 1, 2‐hydrogen migration. Secondly, β‐keto esters have been converted to imidazo[1, 2‐a]pyridine‐3‐carboxylates by using N ‐bromosuccinimide and 2‐aminopyridines in a one‐pot fashion. Abstract : The aldol type condensation reaction of ethyl diazoacetate with aldehydes has been successfully carried out in WEB‐DMSO for the first time producing a library of structurally diverse α‐diazo‐β‐hydroxy esters in very good to excellent yields. Further, two one‐pot sequential reactions including the one‐pot conversion of α‐diazo‐β‐hydroxy esters to β‐keto esters via Pd catalyzed 1, 2‐hydrogen migration reaction and the one‐pot synthesis of imidazo[1, 2‐a]pyridine‐3‐carboxylates have been developed in the same reaction medium.